PERSONAL INCOME TAX: PRACTICE AND PROBLEMS OF MANAGEMENT IN LOCAL BUDGETS OF UKRAINE (INNOVATIVE ECONOMY, 2019)
Karpyshyn N.I., Nipialidi O.Yu. PERSONAL INCOME TAX: PRACTICE AND PROBLEMS OF MANAGEMENT IN LOCAL BUDGETS OF UKRAINEPurpose. The aim of the article is investigation of the practice of tax income on individuals in the local budgets of Ukraine in the context of decentralized reform in order to identify the most pressing problems of collecting PITs and develop a proposal to increase its fiscal role at the local level.Methodology of research. The following methods are used to achieve this goal: analysis, synthesis and generalization – in the processing of literary, statistical, legislative and Internet sources on the topic of research; methods of systematization and generalization of data, comparison and detail – when conducting analysis of budget indicators; graphical and tabular methods – for visual representation of the processed data; abstract and logical method – to summarize the material presented and formulate conclusions.Findings. The fiscal role and factors of PIT growth in the local budgets of Ukraine during the period of decentralization reform have been determined. Local governments are found to be underutilizing the potential of PITs to replenish local budgets. The main reserves for the growth of local budget revenues from the PIT are substantiated, namely: solving the problem of illegal employment with the aim of legalizing income for taxation, improving cooperation with the SFSU bodies and improving the efficiency of tax control; improving community asset management; increasing transparency and enhancing community involvement in community governance.Originality. The main directions of activity of local self-government bodies that will contribute to the gradual increase in the volume of revenues from the personal income tax in the revenues of local budgets of Ukraine are identified.Practical value. The results of the study can be used in the activities of local governments and local financial authorities in developing a policy of increasing PIT (personal income tax) revenues in local budget revenues.Key words: personal income tax; local budgets; local budget revenues; local governments.
Keywords: Key words; personal income tax; local budgets; local budget revenues; local governments.